Influence of irrigation depth and interval under drip irrigation method on productivity of rabi groundnut (Arachis hypogaea L.) in water scarce regions: INFLUENCE OF IRRIGATION DEPTH AND INTERVAL ON PRODUCTIVITY OF RABI GROUNDNUT - Y PADMALATHA; K BHARGAVI; G NARAYANASWAMY (Journal of Oilseeds Research, 2016)
Due to depletion of underground water, the farmers have been facing many problems in irrigating the crops by traditional methods. In such situations, the drip method ofirrigation proved efficient. However, to identify optimum irrigation depth and suitable irrigation interval under drip method of irrigation to rabi groundnut, field experiments were conducted during rabi 2006-07 to 2007-08 with two irrigation depths viz., 10 mm and 15 mm each scheduled at 3 intervals i.e. on 2nd day, 3rd day and 4th day and were compared with traditional check-basin method. In both the years, significantly higher pod yield was recorded with 10 mm depth of irrigation, scheduled on every third day which was at par with 15 mm depth given on 3rd day and 15 mm depth of irrigation on 2nd day. Significantly lowest groundnut pod yield was with check basin method at IW/CPE 1.0, which was 187% and 21% lower than that of 10 mm depth scheduled on 3rd day during 2006-07 and 2007-08, respectively. Highest field water use efficiency was with 10 mm depth of irrigation scheduled on 3rd day during 2006-07 (7.7 kg/hamm) and 10 mm depth scheduled on 4th day during 2007-08 (5.0 kg/hamm). When the quantity of irrigation water available is equal to that of check basin method, irrigations could be scheduled with 10 mmdepth of water on every 4th day so that 136 times additional area could be brought under similar set of irrigation treatment. Thus, the reduction in pod and haulm yields with this treatment could be compensated by bringing additional area through diverting the saved water.